Peran Gagasan dalam Cerpen “Anjing” Karya Kuntowijoyo: Analisis Todorov - Triadnyani, I Gusti Ayu Agung Mas (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 1 (2021), 2021)
This paper aims to investigate the ideas contained in the short story entitled “Anjing” by Kuntowijoyo. There are two views of society towards dogs. On the one hand, this animal is considered an animal that is loyal to his master, on the other hand dog are often considered a disturbing animal and has a negative connotation. This short story describe how dog can affect the lives of neighbors. The method used is an analytic descriptive method. The theory used is narratologi from Todorov. The result obtained is through living as neighbors, we learn to respect the right of other people